The role of Ube3a in neuronal development - Resende, Carlos Manuel dos Santos (2023)
Angelman syndrome (AS) is a genetic disorder characterized by paternal imprinting and maternal deletion of Ube3a. Therefore AS patients have reduced levels of expression of Ube3a in several regions of the brain including the hippocampus and cerebellum. AS patients have motor impairment, mental retardation and absence of speech. Ube3a is an E3 ligase responsible for the ubiquitination of protein leading to the proteasomal degradation and the lack of function as been associated with loss of synaptic plasticity. Although there’s been the identification of several Ube3a substrates with important role in the postsynapse the role of presynaptic Ube3a and the symptoms found in AS patients is still not clear. Ube3a transcription is induced by synaptic activity and glutamate release during early stages of development, indicating that neuronal excitability is important to regulate Ube3a activity. Nonetheless, Ube3a role in excitatory synapse formation and maturation is still not clear. In this work we did a subcellular characterization of Ube3a expression in several regions of Rat and Mouse hippocampal neurons. We observed that Ube3a is expressed at high levels within the nucleus of hippocampal neurons but is also present in the cytoplasm and along the axon. Our results show that Ube3a is highly expressed in the presynaptic compartments of neurons in early stages of development followed by a decrease in the later stages of development. Furthermore, we show that expressing a catalytic inactive form of Ube3a in rat embryonic hippocampal neurons disrupts synapse formation and maturation. Our data suggests that Ube3a catalytic function is necessary for promoting excitatory synapse formation. Collectively, these data contributes to a deeper understanding of the cognitive alterations found in patients with Angelman Syndrome.